Analisis Price, Brand Image, Product Quality Terhadap Purchase Decision Produk Erspo pada Aplikasi Shopee - Muhammad Aditya Ramadhani; Agung Kresnamurti Rivai; Shandy Aditya (Indo Publishing, 2025)
This research is to analyze the variables price, brand image, product quality towards purchase decision of Erspo products on Shopee Application. The study uses a quantitative research design with a survey approach. The population in this study is DKI Jakarta Residents using the Shopee Application who have ever made a purchase of Erspo products. Data analysis on this quantitative research started with composing the description of the data, the process of presenting the data of each variable that is the object of the study as well as performing the calculations and calculations used to answer the formulation of the problem and also testing the hypotheses that have been written. In this study, the researchers used data analysis techniques with SPSS to process the collected primary data, the authors used data analysis techniques through statistical tests. The results of the study found that simultaneously, the independent variables (Price, Brand image, Product quality) have a significant influence on the dependent variable (Purchase decision). Thus, a significance value of ≤ 0.05 indicated that the regression model used was valid and could explain the influence of the independent variables on the dependent variables significantly. This shows that the factors Price, Brand image, Product quality jointly make a meaningful contribution in influencing Purchase decision H4 is accepted.